Prevalence of Migraine Headache Among an Optometry Clinic Patient Sample - Mousa, G Y; Woodruff, M E; Pierson, M A (Canadian Journal of Optometry, 1984)
The objectives of this investigation were: 1) to determine the prevalence of migraine among patients seen at the Optometry Clinic at the University of Waterloo, 2) to compare the prevalence of migraine in this clinical population to that of other studies, 3) to examine the correlation of migraine with observed ocular conditions and medical problems reported by the subjects.